Urgent splenectomy in the course of prosthetic valve endocarditis - Marcinkiewicz, Anna; Ostrowski, Stanisław; Pawłowski, Witold; Palczak, Artur; Kośmider, Adamek; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
We present a case of a 51-year-old male patient hospitalized due to acute coronary syndrome requiring stent implantation to the left main stem. Double antiplatelet therapy was commenced. After 2-3 days, the patient presented with high fever, dyspnea on exertion, pain in the chest, myalgia, and general weakness. Transthoracic (TTE) and transesophageal (TEE) echocardiography revealed abnormal, turbulent flow across the aortic prosthesis, which was probably caused by the presence of a pathological smooth and mobile structure (10 x 9 x 5 mm) in front of the aortic annulus. Blood cultures were positive and staphylococcal prosthetic valve endocarditis (PVE) was diagnosed. Despite antibiotic treatment, the patient’s condition deteriorated, and he was referred for prosthesis reimplantation. After being transferred to the Cardiac Surgery Clinic, he presented with nausea, vomiting, and abdominal pain. The results of imaging examinations suggested spleen hematoma. The patient underwent an urgent splenectomy. Histopathological examination revealed a spleen infarction consequent to an embolic event and subscapular hematoma. On the 10th day after the laparotomy, cardiac surgery was performed. No large vegetations were found on the aortic prosthesis. The mechanical valve, implanted 20 years earlier, was functioning properly; it was intact and well healed. Several fragments of a thrombus and fibrous tissue, resembling a pannus and covered with minor calcifications, were removed from the ventricular surface of the discs. A decision was reached to leave the aortic prosthesis in situ. The valvular material culture revealed the presence of Streptococcus anginosus, and the antibiotic scheme was modified. The postoperative period was uneventful.